Place Names of Illinois - Callary, Edward (Book collections on Project MUSE., 2009)
"Organized alphabetically, the entries are concise, engaging, and full of fascinating detail revealing the rich ethnic history of the state, the impact of industrialization and the coming of the railroads, and insight into local politics and personalities. Many entries concern the names of currently populated places, providing information on local pronunciation, the name's etymology, and the community's location, all set in historical and cultural context. The volume also introduces natural and constructed points of interest such as lakes and airports whose names reflect aspects of the state's history. A general introduction locates Illinois place names in the context of general patterns of place naming in the United States." "An extremely useful reference for scholars of American history, geography, language, and culture, Place Names of Illinois also offers intriguing browsing material for the inquisitive reader and the curious traveler."--Jacket.